A soldier's story = Sergeant Waters - eine Soldatengeschichte = Historia de un soldato = Storia di un soldato - Hancock, Herbie 1940- (Columbia Tristar Home Entertainment, 2006)
A black army attorney is sent to Fort Neal near the end of WW II to investigate the murder of Sgt. Waters, a black man who despised his own roots.